Oxidative DNA Damage from Nanoparticle Exposure and Its Application to Workers' Health: A Literature Review - Kyung-Taek Rim; Se-Wook Song; Hyeon-Yeong Kim (Elsevier, 2013)
The use of nanoparticles (NPs) in industry is increasing, bringing with it a number of adverse health effects on workers. Like other chemical carcinogens, NPs can cause cancer via oxidative DNA damage. Of all the molecules vulnerable to oxidative modification by NPs, DNA has received the greatest attention, and biomarkers of exposure and effect are nearing validation. This review concentrates on studies published between 2000 and 2012 that attempted to detect oxidative DNA damage in humans, laboratory animals, and cell lines. It is important to review these studies to improve the current understanding of the oxidative DNA damage caused by NP exposure in the workplace. In addition to examining studies on oxidative damage, this review briefly describes NPs, giving some examples of their adverse effects, and reviews occupational exposure assessments and approaches to minimizing exposure (e.g., personal protective equipment and engineering controls such as fume hoods). Current recommendations to minimize exposure are largely based on common sense, analogy to ultrafine material toxicity, and general health and safety recommendations.